Temporal variation in saffron (Crocus sativus L.) - DHAR, S K LATTOO, R SAPRU DHAR, A K (Journal of Spices and Aromatic Crops, 1997)
Saffron (Crocus sativus L. : Irridaceae), the world’s most expensive spice is unknown in the wild state (Mathew 1982). It is a triploid (2n=3x=24) and reproduces asexually through corms. In India saffron is cultivated in the Kashmir Valley and also at Kishtwar (Jammu and Kashmir), Ranikhet and Chamoli (Uttar Pradesh). The present investigation was undertaken to assess the temporal variation in saffron from four locations (Chrar-Sharief, Sanatnagar, Pampore and Malabagh). Observations on floral characters were recorded from 200 randomly selected flowers at each location during October-November 1988. The characters included fresh flower weight, flower size (perianth area), stigma length, fresh and dry stigma weight and saffron percentage.